Perancangan Tata Letak Laboratorium Analisis Udara di PT. East Jakarta Industrial Park - Luqyana Assiddiqi (JIE Scientific Journal on Research and Application of Industrial System, 2016)
PT. East Jakarta Industrial Park (EJIP), located in Cikarang, needs to expand their air quality laboratory for providing the air quality check services. These services are provided for all companies located in EJIP area. This company is needed to develop a laboratory layout. Thus, this research is performed for generating several layout alternatives. The input data are process flow, bill of materials, test lists, equipment and processing times. The calculations are performed for determining the space requirement, space availability and activity relationship. The generating of layout alternatives is done by using construction algorithm Automated Layout Design Program (ALDEP). The best layout is chosen based on the highest layout score. In addition, the generated layout should follow the “Peraturan Menteri Perindustrian No. 35 Tahun 2010”, states that availability of green area is around 17.36% of total area.